(untitled) (Homoeopathy for All, 2022)
Homoeopathy is a 200-year-old form of alternative medicine that stimulates a healing response and strengthens the body’s ability to heal itself. Many students now choose to pursue degree course to become homoeopathic doctors. In the past, a candidate was required to pass the 10+ 2 or other equivalent exam with 50% marks, after 12 years of study with the last 2 years of study comprising Physics, Chemistry and Biology to secure admission in BHMS course. Now, admissions to BHMS/MD Courses are done on the basis of National Eligibility cum Entrance Test that is conducted by the Central Board of Secondary Education(CBSE).